SENTIMEN ANALISIS REVIEW PENGGUNA MARKETPLACE ONLINE MENGGUNAKAN NAÏVE BAYES CLASSIFIER - Siti Rahayu; Kusrini Kusrini; Heri Sismoro (Informasi Interaktif, 2018)
The presence of social media allows users to freely review, comment on works, public figures, products, and companies. This is why then social media now is become a great source of data, which can be collected for some analysis , according to information needed. One of them is , Social media data can be used to evaluate the fast-growing market-place website in Indonesia. This can be done by analyzing the sentiments of the users review in social media sites especially twitter. The object of this research is marketplace Online Shoope. The activity of analyzing and processing user review data can also be referred to as Sentiment analysis / opinion mining. One method of text mining that can be used to solve the problem mining issue is Naïve Bayes Classifier (NBC). NBC can be used to classify opinions into positive and negative opinions. The level of accuracy of sentiment analysis system of user review of Marketplace Online shopee by using Naïve Bayes Classifier is 78,3% , with 47 tweets are classified accurately from the total number of testing tweet as much as 60 tweets, with the amount of training data are 300 tweets.Keywords: Naïve Bayes Classifier, Sentiment Analysis, Marketplace Online